ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEPUTUSAN INVESTASI DENGAN GROWTH OPPORTUNITY SEBAGAI MODERATING VARIABEL - I Dewa Made Endiana (Universitas Pendidikan Nasional, 2017)
Investment decisions for shareholders are important because investment is an indicator of the company's existence. The growth of the company is expected to provide a positive aspect for the company so as to increase the chances of investing and the company's survival. This study aims to examine the effect of investment opportunities on investment decisions, to examine the effect of profitability on investment decisions, to examine the effect of dividend policy on investment decisions, to examine the effect of debt policy on investment decisions, and to examine whether growth opportunities can effect investment opportunity, profitability, dividend, And debt policy to investment decisions.This research is focused on companies that listed in Indonesia Stock Exchange for period 2013-2015. Sampling method used is purposive sampling and sample of 46 companies. The technique of data analysis using multiple linear regression and moderated regression analysis (MRA)The result of the research shows that investment opportunity has positive effect on investment decision, profitability has positive effect on investment decision, dividend policy has no effect on investment decision, debt policy has positive effect on investment decision, growth Opportunity can influence relationship between investment opportunity and investment decision, growth Opportunity Able to influence the relationship between profitability with investment decision, growth Opportunity not able to influence the relationship between dividend policy with investment decision, and growth Opportunity able to influence the relationship between debt policy with investment decision.Keyword: Investment, Growth, Opportunity, Dividen, Profitability